A comprehensive analysis of dry eye disease clinical trials (2000–2024): research trends and gaps - Jiang, Xiaohui; Xu, Boyue; Xu, Ruxin; Wu, Nanxin; Tian, Shudong; Peng, Haotian; Zhao, Yun-e (Frontiers in Pharmacology, 2026)
IntroductionDry eye disease (DED), also known as keratoconjunctivitis sicca (KCS), imposes a substantial global burden, yet the clinical trial landscape guiding therapeutic development remains incompletely characterized.MethodsWe conducted a cross-sectional study mapping interventional dry eye disease trials (2000–2024) indexed in Trialtrove. We analyzed 1,171 prospectively registered trials with dry eye disease as the primary indication, characterizing design, phase, geography, sponsorship, endpoints, and therapeutics.ResultsTrial activity rose steadily, peaking in 2023–2024, and was concentrated in the United States (n=773), followed by India (n=111), China (n=71), and Japan (n=58). Sponsorship was balanced between industry (45.5%) and academia (44.4%). Most trials were completed and in later phases (Phase 4: 40.3%; Phase 2: 25.0%; Phase 3: 17.0%). Adult cohorts predominated, yet 59.9% did not report severity strata, and where strata were prespecified, thresholds based on symptom questionnaires were heterogeneous. Monotherapy designs were most common (71.6%), with head-to-head comparisons in 22.4%. Frequently studied interventions included other ocular medications, ocular anti-inflammatory agents, and artificial tears. Primary endpoints centered on ocular surface staining, with the Ocular Surface Disease Index, tear film break-up time, and Schirmer’s test commonly used.DiscussionThese commonly used endpoints vary in psychometric validity and standardization, which can undermine data quality, complicate analysis and interpretation of individual trial results, and limit cross-trial comparability. Overall, the ecosystem appears mature but conservative, emphasizing later-phase, single-agent studies, traditional endpoints, and limited severity stratification and geographic diversity. Future trials should prespecify severity and subtype strata, use validated mechanism-aligned endpoints with standardized assessment windows and longer follow-up, and broaden geographic representation to improve generalizability and cross-trial comparability.